Hyperoxia Leads to Transient Endocrine Alterations in the Neonatal Rat During Postnatal Development - Mirjam Kowallick; Meray Serdar; Boyka Markova; Eva Salveridou; Ursula Felderhoff-Müser; Dagmar Führer-Sakel; Heike Heuer; Ivo Bendix; Monia Vanessa Dewan (Frontiers Media S.A., 2021)
Introduction: High oxygen concentrations have been identified as one factor contributing to the pathogenesis of the retinopathia of prematurity, chronic lung disease of the preterm infant and preterm brain injury. Preterm infants also show short- and long-term alterations of the endocrine system. If hyperoxia is one pathogenetic factor has not been investigated yet. With regard to the high prevalence of neurodevelopmental impairments in preterm infants, the hypothalamus-pituitary-thyroid (HPT) axis, the hypothalamus-pituitary-adrenal (HPA) axis and the hypothalamus-pituitary-somatotropic (HPS) axis are of special interest due to their important role in neurodevelopment.Objective: The aim of this study was to investigate the effect of hyperoxia on the endocrine system in the neonatal rat by analyzing the activities of the HPT, HPA and HPS axes, respectively.Methods: Three-days old Wistar rats were exposed to hyperoxia (oxygen 80%, 48 h). On postnatal day 5 (P5) and P11, transcript levels of thyroid-stimulating hormone (TSH), proopiomelanocortin and growth hormone (GH) were analyzed in pituitary sections by in situ hybridization. Serologic quantification of TSH and thyroxine (T4), adrenocorticotropic hormone and GH were performed by Multiplex analysis and Enzyme-linked Immunosorbent Assay.Results: At P5, significantly lower GH levels were observed in pituitaries (mRNA) and in sera of rats exposed to hyperoxia. Serum TSH was significantly elevated without changes in T4.Conclusion: This is the first study demonstrating transient endocrine alterations following hyperoxia in the neonatal rat making oxygen a possible contributor to the pathogenesis of endocrine alterations seen in preterm infants. Considering the detrimental multi-organ effects of hyperoxia on the immature organism, a rational use of therapeutic oxygen in the treatrnent of preterm infants is of utmost importance.